2013
DOI: 10.1111/1750-3841.12169
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Contains IgE‐Binding Epitopes Sensitive to Periodate but Not to Enzymatic Deglycosylation

Abstract: Glycosylation has been reported to affect the epitopes of food allergens, however, there are few reports on its role in crab allergen. In the present study, the effect of glycosylation on the IgE-binding activity of tropomyosin (TM), a major allergen in Scylla paramamosain, was investigated. The results showed that TM was a glycoprotein with a 0.2% carbohydrate moiety and contained O-glycan. Moreover, enzymatic deglycosylation of TM by glycosidase had no effect on the IgE-binding activity of TM. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…17,29,30 Our previous studies also showed that the digestion products of TM still maintained the ability of sensitization. 35,36,43,44 This was the reason that TM had the ability to activate an allergic reaction after gastrointestinal digestion. In a similar manner, the peptides of Ara h 1 retained both their ability to sensitize and to elicit an allergic reaction after digestion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…17,29,30 Our previous studies also showed that the digestion products of TM still maintained the ability of sensitization. 35,36,43,44 This was the reason that TM had the ability to activate an allergic reaction after gastrointestinal digestion. In a similar manner, the peptides of Ara h 1 retained both their ability to sensitize and to elicit an allergic reaction after digestion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…When combined with heating (90 • C), the maximum reduction of IgG-binding ability was 85.1%. However, Ruan et al (2013) added glycosidase to cleave the O-linked disaccharides, and they found that enzymatic deglycosylation with this kind of enzyme did not affect the IgE-binding activity of TM.…”
Section: Enzymolysismentioning
confidence: 99%
“…However, Ruan et al. (2013) added glycosidase to cleave the O‐linked disaccharides, and they found that enzymatic deglycosylation with this kind of enzyme did not affect the IgE‐binding activity of TM.…”
Section: Modification On Tmmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for allergens with shared epitopes (i.e., glycosylation) [ 40 ]. This issue has raised concerns over whether the group 10 proteins are bona fide HDM allergens, as it is known that tropomyosin has IgE-reactive glycosylation sites [ 41 ]. Aki et al [ 28 ], who discovered Der f 10, noted that the IgE-binding of recombinant Der f 10 was 25× less than the IgE-binding of the native protein, which could indicate differences in glycosylation as proteins synthesized in E. coli lack such modifications.…”
Section: Discovery Phasementioning
confidence: 99%